Research Progress on Electrochemistry Semiconductor Properties and TestMethods for Passivation Films on Iron - Based Materials - TAN Yu, ZHANG Hao, SUN Chen-hao, JIAO Yang, ZHANG Sheng-han, LIANG Ke-xin (Cailiao Baohu, 2021)
Iron-based materials are a class of materials which are widely used in daily life and production, benefiting from their higher mechanical strength, better environmental compatibility and lower prices. The long service performance of iron-based materials in various environments depends on their ability to withstand environmental erosion, which means corrosion resistance, and corrosion resistance is highly correlated with its surface properties. In order to improve the corrosion resistance of iron-based materials, alloy elements were added to develop different series iron-based materials for different occasions like stainless steel, weathering steel, Hastelloy or other as ones. The addition of elements not only changed the metal mutual melt characteristics, but also made the iron-based material surface form a protective ‘passive film’, thereby enhancing its corrosion resistance properties. The passive film on iron-based material surface usually had the characteristics of a semiconductor, its behavior could be obtained by electrochemical analysis test. In this paper, the methods of photoelectrochemical response and AC impedance were introduced in the evaluation of semiconductor properties of passivation film, respectively, and the performance of passive film formed on pure iron, pure chromium, pure nickel and stainless steel in various environments were discussed.